Distal limb desensitisation following analgesia of the digital flexor tendon sheath in horses using four different techniques. (21st November 2013) - Jordana, M.; Martens, A.; Duchateau, L.; Vanderperren, K.; Saunders, J.; Oosterlinck, M.; Pille, F.
Summary Reasons for performing study Controversy exists about the desensitisation obtained after diagnostic analgesia of the digital flexor tendon sheath (DFTS) during lameness examinations. Objectives To determine whether DFTS analgesia results in inadvertent desensitisation of the palmar/plantar digital nerves and whether this depends on the injection technique used. Study design Crossover experimental study. Methods The DFTS of 9 horses were injected with local anaesthetic solution and radiodense contrast medium using one of the following techniques: Proximal (at lateral proximal recess of the DFTS), Axial (axial to the lateral proximal sesamoid bone), Base (at base of the lateral proximal sesamoid bone), and Distal (at palmar/plantar mid‐pastern). In total, 72 injections were performed. Skin desensitisation at the heel bulbs was tested with a dynamometer before and at 15, 30, 90 and 120 min after injection. Results Overall, complete desensitisation of a heel bulb at one or more time points after injection occurred in 22 limbs (30.6%). An additional 7 limbs were partially desensitised. Complete skin desensitisation occurred in 10, 3, 4 and 5 limbs using the Proximal, Axial, Base and Distal techniques respectively. Significant differences between techniques were only found at T30. The probability of skin desensitisation at the heel bulbs was 4 times higher when using the Proximal compared with the Axial and Base techniques in the forelimbs, and 3 times higher compared with the Axial and Distal techniques in the hindlimbs. Skin desensitisation nearly always occurred exclusively on the lateral heel bulb. Bilateral desensitisation only occurred in 5 limbs. Conclusions Anaesthesia of the palmar/plantar digital nerves with distal limb desensitisation often occurs after DFTS analgesia. A higher chance of desensitisation exists when injecting the proximal DFTS recess. It is advisable to verify skin sensitivity at the heel bulbs after DFTS analgesia to avoid false interpretations about the origin of pain causing lameness.